5‐3: Distinguished Paper: Power Saving through State Retention in IGZO‐TFT AMOLED Displays for Wearable Applications. Issue 1 (May 2017) - Steudel, Soeren; van der Steen, Jan-Laurens P.J.; Nag, Manoj; Ke, Tung Huei; Smout, Steve; Bel, Thijs; van Diesen, Karin; de Haas, Gerard; Maas, Joris; de Riet, Joris; Rovers, Madelon; Verbeek, Roy; et al.
Abstract : We present a qHD (960x540 with 3 sub‐pixels) top‐emitting AMOLED display with 340ppi resolution using a self‐aligned (SA) IGZO TFT backplane on polyimide‐foil with humidity barrier. The back plane process flow is based on a 7 layer photolithography process with a CD=4um. We implement a 2T1C pixel engine and use commercial source driver IC made for LTPS. By using IGZO TFT and leveraging the extremely low off‐current, we can switch‐off the power to the source and gate driver while maintaining the image un‐changed for several minutes. We demonstrate that, depending on the image content, low‐refresh operation yields reduction in power consumption of up to 50% compared to normal (continuous) operation. We show that with further increase in resolution, the power saving through state retention will be even more significant.